Prolonged caffeine intake decreases alveolar bone damage induced by binge-like ethanol consumption in adolescent female rats - Maia, Cristiane (2020)
Ethanol consumption has been reported to negatively impact on periodontal disease. In particular, oral cavity disorders occur upon ethanol exposure during adolescence, a life period associated with particular patterns of short and intense ('binge-like') ethanol consumption that is most deleterious to oral health. The hazardous central effects of ethanol have been linked to the overfunction of adenosine receptors, which are antagonized by caffeine, a bioactive substance present in numerous natural nutrients, which can also modify bone metabolism. The aim of this study was to investigate the effects of caffeine on alveolar bone damage induced by an ethanol binge drinking paradigm during adolescence. Female Wistar rats (35 days old; n = 30) were allocated to six groups: control (vehicle), ethanol (3 g/kg/day; 3 days On-4 days Off challenge), caffeine (10 mg/kg/day), caffeine plus ethanol, SCH58261 (0.1 mg/kg/day, an antagonist of A2A receptors), and SCH58261 plus ethanol. Bone micromorphology and vertical bone loss were analyzed by computed microtomography. Our data showed that ethanol binge drinking reduced alveolar bone quality, with repercussion on alveolar bone size. This ethanol-induced alveolar bone deterioration was abrogated upon treatment with caffeine, but not with SCH58261. This shows that caffeine prevented the periodontal disorder caused by ethanol binge drinking during adolescence, an effect that was not mediated by adenosine A2A receptor blockade.